The perceptions and attitudes of health workers towards persons with disabilities in the Bekwai Municipality in the Ashanti Region of Ghana - Tagoe, Wilhelmina Naa Lamiley (2017)
A thesis submitted to the Department of Community Health, College of Health Sciences In partial fulfillment of the requirements for the degree of Masters of Science (Disability, Rehabilitation and Development), 2016.